Philip Henry Sheridan papers - Sheridan, Philip Henry, 1831-1888.
Correspondence, letterbooks, telegrams, memoir, speeches, reports, orders, financial records, scrapbooks, and other papers relating primarily to the Civil War, Reconstruction, Mexican border disputes, Indian wars, and Sheridan's service as commanding general of the U.S. Army.
Civil War material relates to cavalry operations, the Appomattox, Shenandoah, and Tullahoma campaigns, the Winchester Raid, and engagements at Boonville, Chickamauga, Missionary Ridge, Perryville, Ripley, and Stone River. Also includes material on George A. Forsyth's Europe-Asia tour (1875-1876), the Piegan Expedition (1869-1870), Gouverneur K. Warren's court of inquiry (1881), Rebecca M. Bonsal's service as Union spy at Winchester, Va., reconnaissance of the Bighorn Mountains and the Bighorn and Yellowstone river valleys (1877), and Henry Page's service as quartermaster of the Army of the Potomac (1863-1865). Correspondents include George A. Forsyth, James W. Forsyth, Ulysses S. Grant, Abraham Lincoln, Michael V. Sheridan, and William T. Sherman.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts.
Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bonsal, Rebecca M; Forsyth, George A. -- Correspondence; Forsyth, James W. -- 1836-1906 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Page, Henry, -- active 1863-1865.; Sheridan, Michael V. -- 1840-1918 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Warren, G. K. -- 1830-1882.; Courts-martial and courts of inquiry; Indians of North America -- Government relations; Indians of North America -- Wars; Indians of North America -- Wars -- Montana; Piegan Indians -- Wars -- Montana; Reconstruction (U.S. history, 1865-1877); Shenandoah Valley Campaign, 1864 (May-August); Appomattox (Va.) -- History; Asia -- Description and travel; Bighorn Mountains (Wyo. and Mont.) -- Discovery and exploration; Boonville (Mo.) -- History; Chickamauga (Ga.) -- History; Europe -- Description and travel; Georgia -- History -- Civil War, 1861-1865.; Kentucky -- History -- Civil War, 1861-1865.; Mexico -- Boundaries -- United States; Missionary Ridge (Tenn.) -- History; Mississippi -- History -- Civil War, 1861-1865.; Missouri -- History -- Civil War, 1861-1865.; Murfreesboro (Tenn). -- History; Perryville (Ky.) -- History; Ripley (Miss.) -- History; Shenandoah River Valley (Va. and W. Va.) -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; Tullahoma (Tenn.) -- History; United States -- Boundaries -- Mexico; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Cavalry operations; Virginia -- History -- Civil War, 1861-1865.; Winchester, 3rd Battle of, Winchester, Va., 1864.; Wyoming -- Discovery and exploration; Yellowstone River -- Discovery and exploration; Army officers